PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SPORT YAMAHA R15 DI DEALER PANGGUNG MOTOR SOLO - Siswanta, Ervan Mutaqin, Maya Sekar Wangi & (Transformasi, 2016)
With the opening of global markets, so the employer is required to do improvement of itsperformance in order to fulfill the quality of products or services which is desired by the market(consumers). Consumers is knowing of brand image as the most important part of a product,because the brand image reflects about a product. The research‟saim was to determine theeffect of Brand Image both jointly and partially to Keputusan Pembelian Sepeda Motor YamahaR15 di Dealer pangging Motor Solo. The variables studied were Corporate Image (X1), UserImage (X2) and Product Image (X3) as the independent variable, and KeputusanPembelian (Y)as the dependent variable. The total sample of 100 respondents was taken by AccidentalSampling technique of the population, namely the consumers who use Sepeda Motor SportYamaha R15 Di Dealer Panggung Motor Solo. Statistical analysis method used was multiplelinear regression with data processing tools SPSS version 16. With the constant description of7.902 indicates that when variables Corporate Image, User Image, and Product Imageconstants or 0 then the purchasing decisions of 7.902. To improve Corporate Image by 1 so asto improve the purchasing decision amounted to 0,439. In an ever User Image by 1 so as toimprove the purchasing decision by 0.298. Each additional Product Image by 1 so as to improvethe purchasing decision by 0.385. From the results of the t test variable Corporate Image (X1),User Image (X2), and Product Image (X3) partial effect on purchasing decisions. And theresults of tests F Corporate Image (X1), User Image (X2), and Product Image (X3)simultaneously on purchasing decisions. Thus, the hypothesis can be accepted.Key word: Brand Image, Corporate Image, User Image dan Product Image